Juridical Implications of Establishment of Individual Limited Liability Company Without Notary Deed Referring the Law Concerning Creation of Employment in the Conception of Legal Security - Wijaya, Reno Fahmi (Jurnal Konstatering, 2022)
Act No. 11 of 2020 concerning Job Creation (Job Creation Law) opens opportunities for Micro and Small Enterprises (UMK) to form their businesses in the format of a limited liability company which can be established by one person, known as an individual company. An individual company with limited liability is a legal entity concept similar to a limited liability company based on Act No. 40 of 2007 but of course there are different enforceability given privileges to individual companies. The application of this legal entity aims to encourage MSEs or Micro Small Enterprises to develop, so that by turning into a legal entity, MSE owners will find it easier to get investment from the Bank and more regular management of the company. This thesis examines in more depth the establishment of the individual company itself and the legal implications of the establishment of the individual company. This study uses a normative juridical approach using analytical descriptive research specifications. The type of data in this legal research is normative by using primary legal materials in the form of various laws and regulations relating to the protection and legal responsibility of instrumentary witnesses. And secondary legal materials in the form of journals, both international journals and national journals, opinions of notaries, papers, research reports, articles and literature and electronic literature related to legal protection. As well as tertiary legal materials in this study in the form of legal dictionaries, Indonesian dictionaries and encyclopedias. The data collection method in this study is in the form of literature and the data analysis method used is in the form of qualitative data analysis. Based on the results of research and discussion, that there is a new legal entity, namely an individual company which is a legal entity specifically for MSEs. In accordance with Article 153A of the Job Creation Law, only 1 (one) person can establish an individual company. The establishment of an individual company does not require a notary deed but is replaced by a statement of establishment by simply filling in the form provided by the minister and then registering it with the minister electronically. Individual Limited Liability Company is contrary to the regulations relating to the pre-existing Limited Liability Company. Regarding the organs of the Individual Limited Liability Company Government Regulation Number 8 of 2021, namely only directors and shareholders. This has resulted in legal uncertainty regarding the organs of the Individual Limited Liability Company contained in Government Regulation Number 8 of 2021 with the company organs contained in the PT Law. And Government Regulation Number 8 of 2021 does not stipulate if an Individual Company is filed for bankruptcy.Keywords: Juridical Implications, Individual Limited Liability Companies, Legal Certainty.